WEARABLE HEALTH MONITORING SYSTEM ON SMART WATCH: A COST-BENEFIT ANALYSIS AND ECONOMIC IMPACT ASSESSMENT - Dita Caroline Brilian; Putri Kayla Ihsani (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2023)
This study conducts a qualitative investigation through an extensive literature review to evaluate the economic implications of integrating smartwatch-based health monitoring systems into mainstream healthcare. The primary objective is to understand the cost-benefit dynamics and the broader economic impact of this innovative technology. The methodology involves a comprehensive examination of scholarly articles, research papers, and industry reports, providing insights into the development, integration, and economic assessments of wearable health monitoring systems. The qualitative synthesis of this literature focuses on categorizing and interpreting key themes related to cost efficiency, benefits, and societal impacts associated with the adoption of these systems. The findings reveal valuable insights into the initial investment required for the development and implementation of smartwatch-based health monitoring technologies and their potential long-term benefits, including cost savings through early detection of health issues and improved overall health outcomes. The study contributes to the existing knowledge by offering a nuanced understanding of the economic dimensions of wearable health monitoring systems. The synthesized information aims to guide decision-makers, healthcare professionals, and policymakers in strategically navigating the integration of these technologies into mainstream healthcare practices, fostering a proactive and economically sustainable approach to healthcare management.